STRUCTURE AND METAMORPHISM OF BLUESCHIST ECLOGITE-FACIES ROCKS FROM THE NORTHEASTERN OMAN MOUNTAINS - Searle, M; Waters, D; Martin, H; Rex, D (1994)
The northern part of the Saih Hatat window, Oman, shows high-pressure metamorphic rocks derived from shelf sediments and pre-Permian continental basement, and is atypical of sub-ophiolite metamorphism elsewhere. The high-pressure rocks are divided into structural units originally bounded by foreland-propagating thrusts formed during ophiolite obduction, although now many contacts are backthrusts, normal faults or extensional shear zones. Metamorphic breaks exist across many unit boundaries. A tectonic model relates all the high-P units to a single convergent event in the Late Cretaceous. The As Sifah eclogites were exhumed in two stages: 1) tectonic emplacement against other units at c. 20-25 km depth, and 2) exhumation of the entire high-P zone by culmination collapse after obduction. -from Authors